Potongan Harga, Live Streaming, Dan Online Customer Review Terhadap Minat Beli Konsumen Pada Aplikasi Tiktok Shop - Firda Rona Hafizhoh; Rayhan Gunaningrat; Khabib Alia Akhmad (Pusat Riset dan Inovasi Nasional, 2023)
This research was conducted on students of the Faculty of Law and Business, University of Duta Bangsa Surakarta. The purpose of this study was to determine the effect of discounted prices, live streaming and online customer reviews on purchase intention. The population in this study were students of the Faculty of Law and Business, University of Duta Bangsa Surakarta. The development of technology at this time makes people live all instantaneously, not only consuming products but also selling products through e-commerce. So that a lot of competition arises between content creators to market their products in order to attract consumers' buying interest. This study used a purposive sampling method with the criteria of active law and business students at Duta Bangsa University, Surakarta and having an active TikTok Shop account. Which resulted in a sample of 100 respondents. This research uses instrument test analysis, classical assumption test, hypothesis test, determination test (R square) and multiple linear regression. The purpose of this study is to determine the effect of price discounts, livestreaming and online customer reviews on buying interest in the TikTok shop application, either partially or simultaneously. In this study, all the independent variables are significant and have an effect on the dependent variable, namely buying interest.